농촌의 미래 모습, 농촌공간2020 - 박시현 (한국농촌경제연구원, 2006)
The purpose of this study is to picture the features of Korean rural areas around 2020 in consideration of a variety of rapid changes presently facing rural areas based on probable imaginations of the future. To this end, available statistics were collected to predict meaningful trends at a certain time in the future. In parallel, expert discussions were continuously held on diverse themes relating to the future of rural areas. The results of the expert discussions were utilized to draw up scenarios for future lifestyles of rural residents. The findings of the study on the probable look of Korean rural areas by 2020 are summed up as follows: In the majority of rural areas, agriculture would not be regarded as the most important economic activity. In the market areas related to the daily life of rural residents, service supply would be contracted, but due to the frequent intervention in the public sector, the 'service at your doorstep' would appear for the class of people who can not easily access to the services. It would be easy to see only few young and middle-aged farmers work as full-time rice farmers. Meanwhile, organic farming would continue to be revitalized, and the quality protocols would be voluntarily made and established by farmers. Among the components of a farm household's income, the proportion of government subsidies such as direct payment would surge compared to the current level. The autonomous welfare function of rural communities which has been maintained at the village level would be significantly scaled down or disappear. The mixed living of rural and urban residents, increasing immigration, and the segmentation of farmers by commodity will make the rural society more heterogeneous. Within the rural areas, disparities among small towns would be deepened. The accessibility from the urban to the rural would be dramatically improved. In the meantime, new quasi-public transportation would appear for the rural residents whose access to public transportation is very poor. The opportunities for lifelong learning would become more abundant, greatly contributing to enhancing the quality of life for rural residents. Although the demand for medical services is rising rapidly, it is in question whether the demand could be satisfactorily met in rural areas. It seems that as the boundary of urban areas expands, the 'destruction of unique landscape of rural villages' would grow severe. However, depending on regions, local residents and governments will make active voluntary efforts to preserve their landscape. To make a better future for rural areas, the government does not need to rush in and use policy interventions in various areas. Instead, it should give a priority to systematically organizing existing rural policies which are complicatedly entangled. Furthermore, there are a plethora of more work to do, including the establishment of mid/long-term rural policy visions, the complementation of statistical data serving as the basis for policy making, and the assessment and supplementation of new attempts in rural areas.